2018
DOI: 10.7869/tg.486
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Center Experience with 73 Patients of Adult Choledochal Cyst: An Indian Perspective

Abstract: Background: Aim of the study was to analyze the clinicopathological profile and long-term operative outcomes of patients with choledochal cysts (CDC) undergoing cyst excision. Methods: Clinical data of 73 adult CDC patients managed at a single tertiary care center between January 2010 and December 2016 were retrospectively analyzed. Patients who had undergone complete cyst excision and with a minimum follow-up of 12 months were included for long-term outcome analysis. Results: The male female ratio was approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Other reported hypotheses include oligoganglionosis of the biliary tree, partial biliary obstruction, ductal plate malformation, and sphincter of Oddi dysfunction [3,9,10]. In our study, we found APBDU in 6.6% of the patients only.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Other reported hypotheses include oligoganglionosis of the biliary tree, partial biliary obstruction, ductal plate malformation, and sphincter of Oddi dysfunction [3,9,10]. In our study, we found APBDU in 6.6% of the patients only.…”
Section: Discussionsupporting
confidence: 53%
“…The majority of complications were wound-related, with anastomotic leaks followed by pancreatic fistula in the early phase. In the late phase, anastomotic strictures, cholangitis, adhesive intestinal obstruction, and malignancy were reported [10,12]. The risk of malignancy in biliary cysts exists even after the complete surgical excision, as reported in Korean and Japanese studies, but it was virtually nil in Indian studies so far, which can be attributed to the low incidence of APDBU, complete excision of cyst rather than drainage procedures, and shorter long-term follow-up [10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation